2015
DOI: 10.1186/s12891-015-0489-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of anti–tumor necrosis factor therapy for extra-articular manifestations in patients with ankylosing spondylitis: a meta–analysis

Abstract: BackgroundWe performed a meta-analysis to evaluate the effect of anti–tumor necrosis factor (TNF) therapy on the frequency of extra–articular manifestations (EAMs) in patients with ankylosing spondylitis (AS).MethodsWe searched with the terms ‘ankylosing spondylitis’, ‘infliximab’, ‘etanercept’, ‘adalimumab’, ‘golimumab’, ‘certolizumab’, ‘TNF inhibitor/blocker/antagonists’ or ‘anti-TNF’ on MEDLINE, EMBASE and Cochrane Library for randomized controlled trials (RCTs) of ≥12 weeks with parallel or crossover desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
3
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 46 publications
0
23
3
4
Order By: Relevance
“…In addition, data derived from adverse drugs events reporting (not including cases with AS) have supported this finding 24. In contrast, a recent meta-analysis, based on eight RCT of TNFi in AS, reported a contradictory finding, where ETN appeared to be more effective against uveitis than the monoclonal therapies 19. However, in this latter meta-analysis, none of the RCTs included was designed to specifically investigate the effect of TNFi on AU, and the numbers of AU events were small, which may explain the discrepant results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, data derived from adverse drugs events reporting (not including cases with AS) have supported this finding 24. In contrast, a recent meta-analysis, based on eight RCT of TNFi in AS, reported a contradictory finding, where ETN appeared to be more effective against uveitis than the monoclonal therapies 19. However, in this latter meta-analysis, none of the RCTs included was designed to specifically investigate the effect of TNFi on AU, and the numbers of AU events were small, which may explain the discrepant results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the previous studies have been heterogeneous in both design and in reporting of data, and two meta-analyses incorporating observational studies and randomised controlled trials (RCT) have reported conflicting results 10 19. Additional data are thus needed to elucidate whether TNFi have differential effects with regard to preventing AU.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of uveitis is generally good for those who receive appropriate treatment, but serious complications, including permanent vision loss, may result if left untreated. TNF inhibitors can prevent the recurrence of uveitis . Yet this may be not true for ETN (Table ).…”
Section: Paradoxical Adverse Eventsmentioning
confidence: 99%
“…Антитела к растворимым рецепторам ФНОα (этанерцепт) при лечении пациентов с передним увеитом и АС не противопоказаны и могут быть назначены в отдель-ных клинических ситуациях (непереносимость/неэффек-тивность других препаратов, высокий риск реактивации туберкулезной инфекции, мнение эксперта и др.) [50]. Эф-фективность иИЛ17А (секукинумаб) при лечении передне-го увеита не доказана [7].…”
Section: Iii3 рекомендации по применению генно-инженерных биологичеunclassified